Prognostic value of microRNA-21 in epithelial ovarian carcinoma: A protocol for systematic review and meta analysis. Issue 52 (24th December 2020) - Ji, Kun; Wang, Xiaohua; Zhang, Anqi; Wen, Hongwei
Abstract: Backgroud: The expression of microRNA-21 has been shown to be associated with the prognosis in patients with malignant tumors. However, its prognostic value in epithelial ovarian carcinoma (EOC) remains controversial. This meta-analysis aimed to synthesize available data to clarify the association between microRNA-21 expression levels and clinical prognosis in EOC patients. Methods: Eligible literatures were searched from Embase, Google Scholar, PubMed, Web of Science, Medline, Cochrane Library, China Scientific Journal Database, China National Knowledge Infrastructure, Chinese BioMedical Database and Wanfang Database to identify eligible studies. Papers in English or Chinese published from their inception to November 2020 will be included. Methodological quality for each eligible trial will be assessed by using the Newcastle-Ottawa Quality Assessment Scale. Odds ratios or hazards ratios with corresponding 95% confidence intervals were pooled to estimate the prognosis value of microRNA-21 by using Stata 14.0 and Review Manager 5.3 software. Results: This study will provide a high-quality evidence-based medical evidence of the correlations between microRNA-21 expression and overall survival and disease-free survival. Conclusion: The findings of this systematic review will show the effect of high expression of microRNA-21 on the prognosis of EOC patients. Trial registration number: INPLASY2020110064